Study on the high hydrophobicity and its possible mechanism of textile fabric with structural colors of three-dimensional poly(styrene-methacrylic acid) photonic crystals1. Issue 77 (22nd August 2015) - Liu, Guojin; Zhou, Lan; Wang, Cuicui; Wu, Yujiang; Li, Yichen; Fan, Qinguo; Shao, Jianzhong
<x xml:space="preserve">Abstract</x> The fabrics with P(St-MAA) photonic crystals possess high hydrophobicity and vivid structural colors. The possible mechanism of hydrophobicity and model of water droplets on the resultant fabric are investigated.